2007
DOI: 10.1258/095646207780132398
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of young people in Guyana to HIV/AIDS

Abstract: HIV prevalence in Guyana is the third highest in the Caribbean which, in turn, is the second-most-affected region in the world. Over 2000 young people aged 12-20 years completed self-report questionnaires that examined their knowledge of HIV/AIDS, their attitudes to sexual behaviours and their intentions with regard to virginity and use of condoms. Nearly one-quarter of young people aged 12-14 were sexually active and this rose to over one-third for youths aged 15 years and over, but condoms were only used con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…is is similar to research conducted in South Africa and Trinidad and Tobago, which demonstrated an increase in transmission knowledge about HIV from pre-to postintervention [24]. Another study conducted among young people in Guyana between the ages of 12-20 years in which 95.6% of the respondents also knew that HIV can be transmitted by having sexual intercourse with someone who is HIV positive [25]. In two earlier studies conducted in Trinidad and Nigeria among secondary school students 100% and 83.3% of the respective secondary schools knew that AIDS was transmitted by sexual contact [26,27].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…is is similar to research conducted in South Africa and Trinidad and Tobago, which demonstrated an increase in transmission knowledge about HIV from pre-to postintervention [24]. Another study conducted among young people in Guyana between the ages of 12-20 years in which 95.6% of the respondents also knew that HIV can be transmitted by having sexual intercourse with someone who is HIV positive [25]. In two earlier studies conducted in Trinidad and Nigeria among secondary school students 100% and 83.3% of the respective secondary schools knew that AIDS was transmitted by sexual contact [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…is might account for why the students in the intervention group viewed themselves as being susceptible to contracting HIV. In another study, Guyanese youth who were sexually active thought it was very possible for them to contract AIDS and those who were knowledgeable about AIDS thought there was some possibility they could contract the disease [25]. ese �ndings differ from those reported in a study conducted in rural Jamaica in which adolescents between the ages of 15-18 did not view themselves as being susceptible to HIV consistent with the personal fable of adolescence [31].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Being male was the major risk factor for engagement in sexual activity, early sexual debut, and having multiple sexual partners in 12 studies that assessed gender [2,4,5,6,7,9,27,28,31,33,36,37]. In contrast, females were more likely to have experienced force at first sex, and to exhibit STI symptoms, but were less likely to worry about becoming infected with HIV [2,36,37].…”
Section: The Individualmentioning
confidence: 99%
“…One study noted that females were more likely to use condoms at most recent sexual intercourse, whereas another found that males had greater intentions to use condoms [2,33]. Qualitatively, out-of-school boys stated that their lack of condom use can be attributed to trusting one's partner, not having been taught how to use a condom, and enjoying skin to skin contact; however, these same boys reported that they used condoms when they did not know the partner well [35].…”
Section: The Individualmentioning
confidence: 99%